Memahami Problematik Kejahatan Transnasional: Perdagangan dan Penyelundupan Orang di Cina - Nizmi, Yusnarida Eka (Jurnal Hubungan Internasional, 2016)
This research describes about two kind of human crimes which are related each other trafficking and smuggling people in China. There are three main ideas that will be explored. First, this article analyses the causes and effects of trafficking and smuggling people that controlled by Snakeheads. Second, it focuses on the effects of trafficking in Fujian and Yunnan. Third, it explains the efforts that seriously done by China government in solving trafficking and smuggling people. It is important to examine this topic because trafficking involves horrible exploitations to women and children as the most vulnerable groups in China. Being modern society, trafficking rises as a new slavery in China.